Trade Balance Dynamics: The Role of GDP Growth and Exchange Rate in Indonesia – United States Trade Relations (2000-2023) - Debora Silvia Hutagalung; Fransisco Mezgion Hutauruk; Artha Putri Br Karo; Septri Anisa; Andreas Panjaitan (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This study analyzes the impact of Gross Domestic Product (GDP) growth and exchange rate fluctuations on the dynamics of the Indonesia-United States trade balance between 2000 and 2023. Applying quantitative analysis methods through multiple linear regression, this study utilizes secondary data from institutions such as Statistics Indonesia (BPS), Bank Indonesia, and the World Bank. Key findings indicate that the exchange rate significantly influences the trade balance, while GDP growth does not show a statistically significant effect. Simultaneously, these two variables make a significant contribution, explaining 79.4% of the variation in the trade balance. The study period recorded a shift in the trade balance from a deficit (2000–2014) to a sustained surplus (2015–2023), with a peak surplus recorded at 16.568 billion in 2022. This conclusion emphasizes the crucial role of the exchange rate in strengthening export competitiveness, in contrast to GDP growth, which does not directly shape trade patterns. Policy recommendations include diversifying traded commodities and developing non-traditional export sectors to maintain a performance surplus.